Analysis of Regulatory Impacts on the Disharmonization of Professional Zakat Nisab in Indonesia: A Regulatory Impact Analysis (RIA) Approach - Muhamad Agung Budiarto; Isman; Imron Rosyadi; Abdul Rozak; Muhammad Baasith (ASAS, 2025)
The phenomenon of disharmony in the implementation of professional zakat nisab in Indonesia highlights the discrepancy between existing zakat regulations and the practices applied on the ground. Although Fatwa MUI No. 3 of 2003 and PMA No. 31 of 2019 clearly stipulate that professional zakat is only mandatory for individuals whose income meets the nisab threshold, many zakat institutions fail to verify the nisab properly. This study aims to analyze this phenomenon using the Regulatory Impact Analysis (RIA) approach to evaluate the impact of existing regulations and explore the causes of the discrepancy between regulations and practices on the ground. The method used is a qualitative approach with descriptive analysis, involving interviews with Zakat Amil Institutions (LAZ) and a literature review. The findings show that variations in the application of professional zakat nisab, such as the elimination of nisab or the use of silver nisab, lead to injustice and violate sharia principles. The policy recommendations include implementing mandatory infaq contracts for employees whose income does not reach the nisab, strengthening sharia audit regulations to ensure nisab compliance and proper zakat calculation, and enforcing PMA No. 31 of 2019 more strictly. The novelty of this research lies in applying RIA to analyze the impact of professional zakat regulations and propose policies that align more closely with sharia principles. This study contributes to improving the management of professional zakat in Indonesia to enhance fairness and the effectiveness of zakat distribution